Wspólnotowy i wspólnototwórczy charakter modlitwy - Tatar, Marek (Collectanea Theologica, 2019)
The prayer of a Christian is the subject of his daily care in the process of spiritual development. We can say that without it and its dynamic development it is not possible for the spiritual progress of the Christian and the Church in which he or she lives. It is also a very extensive subject of research and scientific work in the field of theology and especially the theology of spirituality. Hence, it must be treated in a multi-faceted and multi-directional way. Among all the different categories of prayer, community prayer and common prayer are very important. This distinction is necessary because it reveals to us the truth that every prayer has a communal character, but it is not always common. However, prayer celebrated together is the source of Christian life and the Church, and it is the clearest and most readable testimony of faith.